Surface Properties and Osteoblastic Cytocompatibility of Two Blasted and Acid-Etched Titanium Implant Systems with Distinct Microtopography - Pedro Mesquita; Pedro de Sousa Gomes; Paula Sampaio; Gintaras Juodzbalys; Américo Afonso; Maria Helena Fernandes (Stilus Optimus, 2012)
Objectives: The aim of this study is to compare two commercially available screw-type sandblasted and acid-etched (SLA) Ti implant systems from Eckermann Laboratorium S.L., with similar geometry and distinct microtopography, regarding surface properties and osteoblastic cytocompatibility. Material and Methods: Implant I (referred as a conventional SLA system) and Implant II (a system patented as Eckcyte®) were characterized for macro and microtopograpphy, surface roughness and chemical composition. For the cytocompatibility studies, human bone marrow osteoblastic cells were seeded over the implants' surface, and the cell response was assessed for cell adhesion and proliferation, alkaline phosphatase (ALP) activity and matrix mineralization. Results: Implant I presented a rough surface with irregularly shaped and sized cavities among flatter-appearing areas, whereas Implant II exhibited a homogeneous rough microporous surface. Compared to Implant I, Implant II presented higher Ra values (0.8 [SD 0.008] μm and 1.21 [SD 0.15] μm, respectively, P < 0.05) and also increased values of Rz, Rt and Rsm, a more negative value of Rsk, and similar RKu values. XPS showed the expected presence of Ti, O, C and N; Al, Si, F, P and Ca were detected in low concentrations. Implant II exhibited significantly lower Al levels. Both implants supported the adhesion, proliferation and differentiation of osteoblastic cells. Implant II showed a thicker fibrilar cell layer and an earlier onset and more abundant matrix mineralization. Conclusions: The homogeneous rough and microporous surface of Implant II is most probably a main contributor for its improved cell response.